PENGARUH KARAKTERISTIK PEKERJAAN, LINGKUNGAN KERA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT SUKASADA - NI MADE RIANITA; NI KADEK VIRGIANDIKA AGUSTINA PUTRI (GANEC SWARA, 2024)
The Sukasada Sub-district Office is a community service organization that is the center of this investigation. Understanding the nature of labor, what motivates people to work, and the conditions in which they do their jobs were the primary goals of this study. Workers' productivity on the job is directly affected by this. Questionnaires were sent out to gather information. The whole staff of the Sukasada Sub-district Office was surveyed using the saturation sample method for this research. Multiple linear analysis was used to process the data: An employee's performance is positively affected by three factors: (1) their job characteristics; (2) their work environment; and (3) their level of work motivation.